An exploration of the lived experiences of people with alcohol-related harm in Scotland. (4th July 2017) - O'May, Fiona; Gill, Jan; Black, Heather; Rees, Cheryl; Chick, Jonathan
ABSTRACT: Background : Alcohol consumption has posed well-documented problems for Scottish society in terms of morbidity, mortality, and wider societal costs. Objectives: To investigate the lived experiences and drinking behaviors of people with alcohol-related harm in Scotland against a backdrop of recent economic downturn, falling incomes, welfare reform, and changes to state benefits. Methods : As part of a larger Scottish study (2012–2014) of 639 individuals attending hospital or admitted, relating to an alcohol problem, 20 participants completed semistructured interviews about their drinking and purchasing habits that were subjected to thematic analysis. Conclusions : Key themes elucidated participants' everyday drink-related behaviors within their local environment including drinking triggers, sourcing alcohol, resourcing alcohol purchase, and views relating to substitution. The majority of participants had experienced reduced income and adapted their alcohol-purchasing behaviors accordingly, including "trading down" to cheaper alcohol. A reduction in food purchasing and heating was a common outcome, as was falling into, or increasing current, debt. More attention should be paid to the prevalence and accessibility of alcohol within local communities. Ultimately, as long as there is highly visible and easily accessible cheap alcohol, heavy drinkers may struggle to undertake positive steps to reduce their damaging consumption levels.